A dictionary of forensic science / Suzanne Bell - Bell, Suzanne
This dictionary covers a wide range of terms used in the field of forensic science, touching on related disciplines such as chemistry, biology, and anthropology. Case examples, figures, and photographs make it the ideal reference for students and practitioners of forensic science, as well as those with a general interest.